Regulatory roles of microRNAs in insect pests: prospective targets for insect pest control. (August 2021) - Zhang, Qiang; Dou, Wei; Taning, Clauvis Nji Tizi; Smagghe, Guy; Wang, Jin-Jun
Graphical abstract: Highlights: miRNAs play regulatory roles at the post-transcriptional level in insects. miRNAs as key mediators in insect development. miRNAs participate in insecticide resistance and host adaptation. miRNAs as a prospective target in pest control. Transgenic biotechnology is an effective solution for miRNAs application. Abstract : At the post-transcriptional level, microRNAs (miRNAs) play an important role in the regulation of gene expression, thereby influencing the outcome of many biological processes in insects, such as development, reproduction, metamorphosis, immunity, and insecticide resistance. The alteration of miRNA expression by mimic/agomir or inhibitor/antagomir via injection/feeding can lead to pest developmental abnormalities, death, or reduced pesticide resistance, indicating that miRNAs are potential targets for pest control. This review provides an overview of recent advances in understanding the regulatory roles of miRNA in agricultural and public health insect pest, and further highlights the potential of miRNAs as prospective targets in pest control.